Aggressive modulation/coding scheme selection for maximizing system throughput in a multi-carrier system - Talukdar, A.; Sartori, P.; Cudak, M.; Classon, B.; Blankenship, Y. (2005 IEEE 61st Vehicular Technology Conference, 2005)
Multi-carrier modulation techniques, such as OFDM, are attractive propositions for the design of future broadband wireless communication systems due to higher spectral efficiency than CDMA. A capacity enhancing technique to be commonly used in these systems is adaptive modulation/coding (AMC) for link adaptation. With AMC, the modulation and coding scheme (MCS) is selected based on the channel quality information. MCS selection is an imperfect process by nature, due to, for example, the variability of the channel. Moreover, since the set of available MCSs is quantized, it is not always possible to select the optimal rate. Using these non-optimal MCS values results in reduced system capacity. This paper describes a method that attempts to maximize system and user throughputs in a multi-carrier system by overcoming the impacts of such non-optimal MCS selection through the use of hybrid ARQ (HARQ). This method relies on aggressive MCS selection and multiple HARQ transmissions. The performance impact of this method on various types of packet data applications is evaluated by system level simulation. Simulation results indicate that significant system and user throughput gains can be achieved by this method.